Напружно-деформований стан та експериментальне впровадження порожнистих бетонних і залізобетонних конструкцій - Мельник, Ігор Володимирович (Національний університет "Львівська політехніка", 2021)
В дисертації за результатами проведених експериментально-теоретичних досліджень вирішено важливу наукову-технічну проблему вдосконалення і надання більш раціональних форм залізобетонним і бетонним конструкціям масового виготовлення через порожниноутворення та розширення сфери їх використання на практиці і пов’язану з актуальними проблемами матеріало-, ресурсо- і енергозбереження, а також в значній мірі екологічної безпеки. Розроблено методику визначення жорсткостей на згин в обох напрямках монолітного залізобетонного перекриття з однонапрямленими вставками. Обґрунтовано розрахункові схеми і запропоновано методику розрахунку плитних залізобетонних порожнистих конструкцій з двонапрямленими порожниноутворювальними вставками з врахуванням складного НДС бетону. За результатами комплексних натурних випробувань порожнистих блоків та їх малогабаритних моделей отримано експериментальні дані щодо їх фактичної міцності, деформативності і тріщиностійкості та обгрунтувано критерії визначення розрахункової несучої здатності з врахуванням комп’ютерного моделювання в різних сучасних програмних комплексах. В диссертации по результатам проведенных экспериментально-теоретических исследований решена важная научно-техническая проблема совершенствования и предоставления более рациональных форм железобетонным и бетонным конструкциям массового изготовления путем пустотообразования и расширения сферы их использования на практике и связанную с актуальными проблемами материало-, ресурсо- и энергосбережения, а также в значительной степени экологической безопасности. Разработана методика определения жесткостей на изгиб в обоих направлениях монолитного железобетонного перекрытия с однонаправленными вкладышами. Обоснованы расчетные схемы и предложена методика расчета плитных железобетонных пустотелых конструкций с двухнаправленными вкладышами с учетом сложного НДС бетона. По результатам комплексных натурных испытаний пустотных блоков и их малогабаритных моделей получены экспериментальные данные по их фактической прочности, деформативности и трещиностойкости и обоснованы критерии определения расчетной несущей способности с учетом компьютерного моделирования в различных современных программных комплексах. In the Introduction, the choice of the research theme is substantiated, the aim and the tasks of the research are formulated as well as the topicality and practical value of the work. In Chapter 1, the solutions to the construction of the monolithic, precast and composite ceilings, monolithic slab ferroconcrete foundations, ferroconcrete small and medium roadway bearers and hollow concrete foundation blocks are provided, as well as the review of studies and computing methods on the topic. As a result of the review and analysis of existing ferroconcrete and concrete constructions, the tasks of the research have been formulated with the aim of improving these constructions by making them hollow. In Chapter 2 of the thesis, according to the thorough literature and patent studies, the main methods of lessening material and power consumption and labor expenditures for concrete and ferroconcrete constructions are determined. Developed action charts are given for the following ferroconcrete hollow constructions: monolithic ceilings, precast monolithic ceilings, single slab constructions, monolithic slab foundations; ferroconcrete and composite bridge span bearers. Chapter 3 contains the technique and the results of experimental investigations of several types of fragments of monolithic ferroconcrete ceilings and the results of environmental tests of the monolithic ferroconcrete ceiling with foam polystyrene inserts. Experimental investigations have showed that regardless of the kind of prototype units and the way of their loading, their strength and deformability are different. The results of the environmental tests of a large flat monolithic ceiling with the dimensions 7,6х12,1x0,26 m and with prismatic foam polystyrene inserts of a crosssection of 16х16 cm in its middle part are given. In Chapter 4, the developed proposals for the calculation of hardness of ceilings with square, rectangular and round inserts are described. The ceiling with above mentioned shapes of unidirectional inserts was modeled as an orthotropic slab with the use of a finite element method. Design models were substantiated, and the technique for calculating the slab ferroconcrete constructions with bidirectional hollow-forming inserts taking into account plane deflected mode of concrete was proposed. The algorithm of calculating has been developed and an example of calculations given according to the proposed technique for a monolithic ferroconcrete ceiling. In Chapter 5, the results of theoretical and experimental investigations of hollow concrete blocks are described. Carried out environmental tests of hollow foundation blocks with the nominal dimensions 0,4х0,6х2,4 m in the structure of 9 constructions of a three-tier wall made it possible to reveal the peculiarities of their deflected mode and the criteria of their loading capability under the different loading conditions. The satisfactory convergence of the real loading capability of hollow blocks in the structure of 9 walls with theoretical one determined by the simulation in the ANSYS and Lira software facilities was obtained. In Chapter 6, the technological and operational integrity of slab ferroconcrete hollow constructions, concrete hollow foundation blocks is given, as well as their technoeconomic efficiency. Techno-economic characteristics of hollow ceilings confirm the efficiency of the use of inserts, since they cause the considerable decrease in concrete consumption and, correspondingly, in their weight and the amount of reinforcement. A process flow-sheet and the proposals for the manufacturing application of wood concrete inserts which can be widely used in the process of making concrete blocks for cellar walls has been developed. In Chapter 7, using the example of particular buildings, the experience of designing and implementing numerous hollow ferroconcrete and concrete products is shown, whose calculations and design was conducted with the use of the results of carried out theoretical and experimental investigations. First of all, they are monolithic ferroconcrete ceilings widely used at the construction of multistorey skeleton constructions, as well as low-rise buildings. These lightweight ceilings were used in the construction of 28 objects with the concrete saving and proper weight decrease from 18% to 47%. General construction solutions and recommendations for the use of four investigated kinds of hollow blocks for low-rise and mid-rise buildings have been developed.
Напряженно-деформированное состояние и экспериментальное внедрение пустотных бетонных и железобетонных конструкций
Deflected mode end experimental implementation of hollow concrete and ferroconcrete constructions
Keywords: бетонні і залізобетонні конструкції; порожнини; порожниноутворювальні вставки; напружено-деформований стан; експериментальнотеоретичні дослідження; впровадження; бетонные и железобетонные конструкции; пустоты; пустотообразующие вкладыши; напряженно-деформированное состояние; экспериментально-теоретические исследования; внедрение; concrete and ferroconcrete constructions; hollows; hollow-forming inserts; deflected mode; theoretical and experimental investigations; implementation; 624.012.4+691.32